Urticaria and Angioedema: Retrospective Study - Wirantari, Nadia; Prakoeswa, Cita Rosita Sigit (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2014)
Background: Urticaria is a common disorder that often presents with angioedema. Angioedema which may lead to laryngeal involvement, asphyxiation, and urticaria lasting more than 72 hours, are indications of hospitalization. Purpose: To describe the distribution, duration of hospitalization, trigger factor, clinical form, diagnostic, and therapeutic approach in urticaria and angioedema patients in Dermaro-venerelogy Departement Dr. Soetomo General Hospital during year 2011-2013. Methods: Retrospective study using medical records of new patients with urticaria and/ or angioedema in Dermatovenereology Ward st thduring 1 January 2011 until 31 December 2013. Basic data, anamnesis, physical examination, diagnostic, and therapeutic approach are recorded. Results: There were 42 new patients with urticaria and/or angioedema (2.3% of all Dermatoveneorology inward patients), with mean length of stay 4-6 days (57.1%), chief complaint of itch, hives, and swelling (42.8%), lesions occur for less than 6 weeks (92.9%), for the first time (54.8%), with episodes of less than 72 hours (45.3%). Urtica and angioedema were the most often clinical findings (38.1%), complete blood count and urinalysis were routinely examined (100% and 97.6% respectively). Treatment combination of corticosteroid and antihistamin H1 was the most commonly prescribed (64.0%). Conclusion: Urticaria along with angioedema was the most common condition in inward patients, thus combination therapy of antihistamin H1 and corticosteroid were most often needed.Key words: urticaria, angioedema, retrospective study.